Analysis of the mining equipment replacement time. A case study focused on drilling rig - Ana M. Castañón; Juan C. Gutiérrez-Diez; Marc Bascompta (Results in Engineering)
Mining equipment is subjected to degradation throughout its operation lifetime, being the definition of the replacement time for mining equipment a vital question. Requiring accurate information about the performance of the equipment to identify the optimal replacement time. This study determines the replacement time using an improved method, Overall Mining Equipment Effectiveness (OMEE), that analyses the technical factors from mining equipment performance in real-time, such as the technical availability rate, the mechanical availability rate, the production rate and the productivity index. The suitability of the method has been tested using a real open pit mine and information gathered from six drilling rigs, which have been performing around 27,000 engine hours each, over the last twelve years. The results obtained show that the OMME methodology is reliable to analyse the mining equipment performance and determine the technical replacement time.